2010
DOI: 10.1371/journal.pbio.1000396
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila microRNAs 263a/b Confer Robustness during Development by Protecting Nascent Sense Organs from Apoptosis

Abstract: microRNA-263a/b confer robustness to sense organ development by controlling expression of the pro-apoptotic gene hid during apoptotic tissue pruning in Drosophila.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 62 publications
2
94
0
1
Order By: Relevance
“…Indeed, the expression of many miRNAs is developmentally regulated, consistent with roles for miRNAs in the regulation of gene expression in conjunction with developmental processes (Bartel 2004;Kato and Slack 2008). Furthermore, roles for miRNAs in providing robustness of developmental outcomes to various perturbations have been demonstrated (Li et al 2009;Hilgers et al 2010;Rasmussen et al 2010).…”
Section: Introductionmentioning
confidence: 72%
“…Indeed, the expression of many miRNAs is developmentally regulated, consistent with roles for miRNAs in the regulation of gene expression in conjunction with developmental processes (Bartel 2004;Kato and Slack 2008). Furthermore, roles for miRNAs in providing robustness of developmental outcomes to various perturbations have been demonstrated (Li et al 2009;Hilgers et al 2010;Rasmussen et al 2010).…”
Section: Introductionmentioning
confidence: 72%
“…This type of threshold might be important not only in circadian cell determination but also to prevent stochastic or random pulses of CLK-driven activity that could alter or shift the circadian clock. miRNA-mediated thresholding of master developmental regulators has been previously demonstrated for the miR-9a/senseless 61 and for the miR-263a/hid pairs 62 . We believe that our failure to detect signal from the Clk 3 0 UTR reporters is not related to a sensitivity issue.…”
Section: Discussionmentioning
confidence: 94%
“…In total, 18 mutants showed significantly reduced viability (p < 0.01, binomial test, summarized in Table 2). These include bantam, miR-1, the let-7 (miR-100, miR-125) cluster, miR-8, the miR-309 cluster, miR-263a and miR-276a, which have previously been reported to reduce viability (Brennecke et al, 2003;Bushati et al, 2008;Caygill and Johnston, 2008;Ge et al, 2012;Hilgers et al, 2010;Karres et al, 2007;Sokol and Ambros, 2005;Li et al, 2013), as well as several miRNAs for which no viability data have been reported previously.…”
Section: Survival Phenotypesmentioning
confidence: 99%